Enhanced flux and surface modification of PVDF hollow fiber membranes using bamboo cellulose/PVA composite coatings - Perry Law, Nyuk Khui; Rezaur, Rahman; Khairul Anwar, Mohamad Said; Murtala, Namakka; M., Shahabuddin; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed M., Rahman (Springer Nature, 2025)
This study showcases the characterization of cellulose/PVA coating on neat PVDF hollow fiber membrane. The SEM corroborated successful coating of cellulose/PVA with a visible porous surface, webbing type structure, and a coated overlapping layer. The webbing type structure and porous surface correlate with improved water flux performance, while the overlapping layer of coating with visible cracks at higher cellulose content correlates with decreased water flux performance. Fourier transform infrared spectroscopy (FTIR) analysis shows that evidence of cellulose/PVA presence on the coated surface through available hydroxyl groups peaks stretches at the O–H and C–H regions. X-ray diffraction (XRD) analysis shows evidence of amorphous phase on the surface of the cellulose/PVA-coated membrane. This indicated that the coated membrane possesses an improved hydrophilic properties instilled on the modified PVDF hollow fiber membrane. The performance of the modified hollow fiber membrane was tested on different water samples. The performance results corroborated an improved water flux performance for pure, rain, river, and peat water with over four times the recorded value of the unmodified hollow fiber membrane. The best performing membrane is PV01 with pure water flux of 860.735 m2 /Lhbar. The porosity and mean pore size corroborates with the water flux performances. The increased porosity with increased mean pore size allows better permeability. The atomic absorption spectrometry (AAS) analysis shows the iron (Fe) removal capabilities of the coated membranes. The filtered peat water optimally showcases the capability of coated membranes. It was found that as cellulose content increases in the hollow fiber membranes, the percentage of iron removed also increases.